Factors influencing nontraditional students' persistence in online programs for nontraditional students attending a Wisconsin technical college - Hurtienne, Matthew W., author; Gloeckner, Gene, advisor; Hogler, Raymond, committee member; Kaminski, Karen, committee member; Lynham, Sue, committee member (Colorado State University. Libraries, 2015)
The purpose of this study was to determine the factors that play a significant part in online students’ intent to persist at a Wisconsin Technical College. Specifically, this project focused on the relationships between intent to persist and the following variables: GPA, academic advising (concern), academic advising (appointment), education usefulness, student satisfaction, commitment, academic stress, outside encouragement from parents/spouse, outside encouragement from employer, outside encouragement from friends, and financial certainty. Data were collected through an online survey of FLEx students at Moraine Park Technical College in Wisconsin. The nontraditional student attrition questionnaire developed by Metzner (1983) and Bean (Metzner & Bean, 1987) was the instrument for the study. The instrument was used to examine the factors affecting intent to persist for both online and face-to-face students. Because the study included factors that the college may not have direct influence over, a separate analysis was conducted for factors that the college can directly affect. The results of this study showed that education usefulness, outside encouragement from employer, outside encouragement from friend, and financial certainty played important roles in online students’ intent to persist for both internal and external college-controllable variables. For face-to-face students, financial certainty, student satisfaction, academic stress, and outside encouragement by parents or spouse were the most important factors in intent to persist for both internal and external college-controllable variables.
Keywords: non-traditional students; student persistence; technical college; online education; distance education; student retention